PI3Kδ activation, IL-6 overexpression, and CD37 loss cause resistance to naratuximab emtansine in lymphomas - Alberto J. Arribas; Sara Napoli; Eugenio Gaudio; Charles Herbaux; Eleonora Cannas; Chiara Tarantelli; Roberta Bordone-Pittau; Luciano Cascione; Nicolas Munz; Luca Aresu; Jacopo Sgrignani; Andrea Rinaldi; et al. (Blood Advances)
Abstract: CD37-directed antibody and cellular-based approaches have shown preclinical and promising early clinical activity. Naratuximab emtansine (Debio 1562; IMGN529) is an antibody-drug conjugate (ADC) incorporating an anti-CD37 monoclonal antibody conjugated to the maytansinoid DM1 as payload, with activity as a single agent and in combination with rituximab in patients with lymphoma. We studied naratuximab emtansine and its free payload in 54 lymphoma models, correlated its activity with CD37 expression, characterized two resistance mechanisms, and identified combination partners providing synergy. The activity, primarily cytotoxic, was more potent in B- than T-cell lymphoma cell lines. After prolonged exposure to the ADC, one diffuse large B-cell lymphoma (DLBCL) cell line developed resistance to the ADC due to the CD37 gene biallelic loss. After CD37 loss, we also observed upregulation of interleukin-6 (IL-6) and related transcripts. Recombinant IL-6 led to resistance. Anti-IL-6 antibody tocilizumab improved the ADC’s cytotoxic activity in CD37+ cells. In a second model, resistance was sustained by a PIK3CD activating mutation, with increased sensitivity to PI3Kδ inhibition and a functional dependence switch from MCL1 to BCL2. Adding idelalisib or venetoclax overcame resistance in the resistant derivative and improved cytotoxic activity in the parental cells. In conclusion, targeting B-cell lymphoma with the naratuximab emtansine showed vigorous antitumor activity as a single agent, which was also observed in models bearing genetic lesions associated with inferior outcomes, such as Myc Proto-Oncogene (MYC) translocations and TP53 inactivation or R-CHOP (rituximab, cyclophosphamide, doxorubicin, Oncovin [vincristine], and prednisone) resistance. Resistant DLBCL models identified active combinations of naratuximab emtansine with drugs targeting IL-6, PI3Kδ, and BCL2.